Insularities: Anglo- and Asia-centrism in tourism. (September 2021) - Chang, T.C.
Abstract: The universalist discourse of Anglo-centric research in tourism has been criticised for being inward looking. Countering this has been an emergent wave of critical Asian Tourism Studies that offers insights on places, processes and people from an Asian perspective. However, this assertive Asian voice also perpetuates its own insular thought, described here as Asia-centrism. This paper proposes a conceptual schema to advance tourism knowledge that steers clear of centric proclivities, while serving as a guide for future engagement with critical tourism studies. The need for academic activism, the value of culturally sensitive scholarship, the importance of reflexivity and the quest for complex thinking are advocated. Highlights: The paper highlights different forms of 'insularities' in tourism scholarship. The causes of insularities are examined, along with their effects. A Conceptual Schema is offered to steer scholarship away from insular thinking.